2023
DOI: 10.1097/md.0000000000035852
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and molecular docking reveal potential mechanism of esculetin in the treatment of ulcerative colitis

Ting Cai,
Bin Cai

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease of the colonic mucosa. Esculetin is a type of natural coumarin that has many pharmacological activities such as antioxidant, anticancer, anti-inflammatory, etc. A previous study showed that esculetin improved intestinal inflammation and reduced serum proinflammatory cytokines in UC. The present study aimed to utilize network pharmacology and molecular docking to explore the potential mechanism of esculetin against UC. The potential gene targets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that MMP9 was a crucial enzyme involved in gastric ulcers, facilitating tissue repair and participating in the inflammatory reaction (Lv et al, 2024). Recent research indicated that EGFR (Wang et al, 2024) and ESR1 (Cai & Cai, 2023) protein targets improved the disease activity index of colitis mice by inhibiting necroptosis of intestinal epithelial cells. Qu et al ( 2023) have suggested that the activation of AKT1 could potentially induce inflammatory reactions and promote proinflammatory responses.…”
Section: Analysis Of Potential Target and Ppi Networkmentioning
confidence: 99%
“…Previous studies have demonstrated that MMP9 was a crucial enzyme involved in gastric ulcers, facilitating tissue repair and participating in the inflammatory reaction (Lv et al, 2024). Recent research indicated that EGFR (Wang et al, 2024) and ESR1 (Cai & Cai, 2023) protein targets improved the disease activity index of colitis mice by inhibiting necroptosis of intestinal epithelial cells. Qu et al ( 2023) have suggested that the activation of AKT1 could potentially induce inflammatory reactions and promote proinflammatory responses.…”
Section: Analysis Of Potential Target and Ppi Networkmentioning
confidence: 99%